2021
DOI: 10.1002/aic.17182
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of aging process on reduced Ag exchanged mordenite in dry air and humid air

Abstract: Aging effects of off‐gas streams including dry air and humid air on reduced silver exchanged mordenite (Ag0Z) were studied. Aged Ag0Z was prepared by exposing Ag0Z to dry air and humid air at different aging temperatures, time, and water vapor concentrations. Iodine loading capacity on the aged Ag0Z was obtained through a continuous‐flow adsorption system. Significant iodine loading capacity losses were observed after the Ag0Z was exposed to dry air and humid air. Physical and chemical analyses were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…All five samples followed the same I 2loading procedures as described in section 2.1. 19,20,26 Ag 2 S displays the highest uptake capacity in this experiment with a mass gain of ∼86.8 wt %, followed by Ag 0 -aerogel at ∼36.5 wt %, and Ag 0 Z at ∼12.5 wt %. These differences are simply attributable to the different Ag content of each sample (87.1 wt % for Ag 2 S, ∼35.5 wt % for Ag 0 -aerogel, 23 and ∼12 wt % for Ag 0 Z).…”
Section: Examination Of Ag 2 S As An Adsorbent For Imentioning
confidence: 76%
See 4 more Smart Citations
“…All five samples followed the same I 2loading procedures as described in section 2.1. 19,20,26 Ag 2 S displays the highest uptake capacity in this experiment with a mass gain of ∼86.8 wt %, followed by Ag 0 -aerogel at ∼36.5 wt %, and Ag 0 Z at ∼12.5 wt %. These differences are simply attributable to the different Ag content of each sample (87.1 wt % for Ag 2 S, ∼35.5 wt % for Ag 0 -aerogel, 23 and ∼12 wt % for Ag 0 Z).…”
Section: Examination Of Ag 2 S As An Adsorbent For Imentioning
confidence: 76%
“…Our previous studies have focused on the processes governing aging in two prototypical porous Ag adsorbents, Ag 0 Z and reduced Ag functionalized silica aerogel (Ag 0 -aerogel), in gas streams containing the aforementioned off-gas components. 19−22 Ag 0aerogel is a relatively new material developed at Pacific Northwest National Laboratory (PNNL), and its high Ag content and adequate specific surface area aid in iodine capture, making it an appealing alternative to zeolites that have traditionally been the primary focus in this area. 23,24 By exposing Ag 0 Z and Ag 0 -aerogel to gas streams containing the aforementioned off-gas components at 150 °C, we found that NO 2 significantly reduced the I 2 capacity for both materials (∼90% reduction after 1 month), 21,22 while O 2 , H 2 O, and NO were less impactful (30%−80% reduction for Ag 0 Z and ∼20% reduction for Ag 0 -aerogel after 1 month).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations